Secrets in the dark - Coates, Darcy (Coates, Darcy. Black winter, 2020)
"Winterbourne Hall is not safe. Clare and Dorran scramble to secure the ancient building in an effort to protect themselves from the ravenous hollow ones, but that isn't their only concern. Somewhere far away, Beth is alive, but she's trapped, and her oxygen is running out. Hundreds of kilometers separate Clare from her sister. The land between them is infested with monsters, and the roads are a maze of dead ends. She knows she can't survive the trip by herself. But even with Dorran at her side, can she truly hope to face the winter stillness...and make it to her desperate sister before it's too late?"--Provided by publisher.